Clinicopathological characteristics and outcome predictors of anti-glomerular basement membrane glomerulonephritis. Issue 1 (31st December 2022) - Ge, Yifei; Liu, Kang; Yang, Guang; Yu, Xiangbao; Sun, Bin; Zhang, Bo; Yuan, Yanggang; Zeng, Ming; Wang, Ningning; Xing, Changying; Mao, Huijuan
Abstract: Objective: To explore the clinicopathological features of anti-glomerular basement membrane (anti-GBM) glomerulonephritis (anti-GBM-GN) and the prognostic values of clinical and laboratory indicators at diagnosis on renal and patient survival. Methods: A total of 76 patients (34 males and 42 females) with anti-GBM-GN who were hospitalized in the First Affiliated Hospital of Nanjing Medical University between January 2010 and June 2021 were included in this study. The baseline clinical features, histopathological data from renal biopsies, and predictors of renal and patient survival were retrospectively analyzed. Results: Among the 76 patients, the median serum creatinine at diagnosis was 618.0 (350.98, 888.25) μmol/L and the median estimated glomerular filtration rate (eGFR) was 6.62 (4.39, 14.41) mL/min. Of these 76 patients, 55 (72.4%) received initial kidney replacement therapy (KRT) and 39 (51.3%) received plasma exchange or double-filtered plasmapheresis (DFPP). During a median follow-up duration of 28.5 (6.0, 71.8) months, 53 (69.7%) patients progressed to kidney failure with replacement therapy (KFRT) and received maintenance dialysis. Initial KRT (HR = 3.48, 95% CI = 1.22–9.97, p  = 0.020) was a significant risk factor for renal survival. During the follow-up, 49 (64.5%) of 76 patients survived. Age (≥60 years, HR = 4.13, 95% CI = 1.65–10.38, p  = 0.003) and initial KRT (HR = 2.87, 95% CI = 1.01–8.14, p  = 0.047) were predictive of patient survival. Conclusions: Among patients with anti-GBM-GN, initial KRT at presentation was predictive of KFRT while older age and initial KRT were associated with higher all-cause mortality.